2021
DOI: 10.1021/acs.jmedchem.1c00828
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 2-(Ortho-Substituted Benzyl)-Indole Derivatives as Potent and Orally Bioavailable RORγ Agonists with Antitumor Activity

Abstract: RORγ is a dual-functional drug target, which involves not only induction of inflammation but also promotion of cancer immunity. The development of agonists of RORγ promoting Th17 cell differentiation could provide a novel mechanism of action (MOA) as an immune-activating anticancer agent. Herein, we describe new 2-(ortho-substituted benzyl)-indole derivatives as RORγ agonists by scaffold hopping based on clinical RORγ antagonist VTP-43742. Interestingly, subtle structural differences of the compounds led to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Given the critical roles in multiple inflammatory pathways, RORγ inhibition represents an attractive therapeutic strategy to treat inflammatory diseases . Therefore, a large number of RORγ inhibitors with diverse chemical scaffolds have been reported by many research groups and more than 10 candidates have been advanced into clinical trials in patients with inflammatory or autoimmune disease, such as compounds 1 – 6 (Figure ). On the other hand, more recent studies also revealed the critical roles of RORγ in the initiation and progression of various cancers, including multiple myeloma, hepatoma, and colorectal, lung, breast, pancreatic, cervical, and prostate cancers. In CRPC tumors, RORγ is overexpressed and amplified, and functions as a key determinant of AR overexpression and aberrant signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Given the critical roles in multiple inflammatory pathways, RORγ inhibition represents an attractive therapeutic strategy to treat inflammatory diseases . Therefore, a large number of RORγ inhibitors with diverse chemical scaffolds have been reported by many research groups and more than 10 candidates have been advanced into clinical trials in patients with inflammatory or autoimmune disease, such as compounds 1 – 6 (Figure ). On the other hand, more recent studies also revealed the critical roles of RORγ in the initiation and progression of various cancers, including multiple myeloma, hepatoma, and colorectal, lung, breast, pancreatic, cervical, and prostate cancers. In CRPC tumors, RORγ is overexpressed and amplified, and functions as a key determinant of AR overexpression and aberrant signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ( R )-2-((1-(2-(bis(4-methoxybenzyl)amino)pyridin-3-yl)ethyl)amino)ethan-1-ol ( 1 , in Figure ) has been identified as the key intermediate in the synthesis of a series of pan KRAS inhibitors . The synthesis of this chiral secondary amine, however, encountered some challenges when scaling up (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Therefore, RORγt agonists remain potential tactics to cancer immunotherapy as orally bioavailable small-molecule therapeutics. 26 In addition to LYC-55716, a number of RORγt agonists with diverse scaffolds have been disclosed (Figure 1), including Narylsulfonyl indolines by Scripps Research Institute, 27 benzyloxytricyclic compounds by Bristol Myers Squibb, 28 2-(ortho-substituted benzyl)-indoles from Shanghai Hengrui, 29 tertiary amines 30 and biaryl series 31 from GSK, and so on.…”
Section: ■ Introductionmentioning
confidence: 99%